Solution of Finite Difference Method and Differential Quadrature Method in Burgers Equation - Amiruddin Ab. Aziz; Noor Syazana Ngarisan; Nur Afriza Baki (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2019)
The Finite Difference Method and Differential Quadrature Method are used to solve the partial differential equation in Burgers equation. The different number of nodes is used in these methods to investigate the accuracy. The solutions of these methods are compared in terms of accuracy of the numerical solution. C language program have been developed based on the method in order to solve the Burgers equation. The results of this study are compared in terms of convergence as well as accuracy of the numerical solution. Generally, from the numerical results show that the Differential Quadrature Method is better than the Finite Different Method in terms of accuracy and convergence